2022
DOI: 10.1186/s40104-022-00723-1
|View full text |Cite
|
Sign up to set email alerts
|

Small-extracellular vesicles and their microRNA cargo from porcine follicular fluids: the potential association with oocyte quality

Abstract: Background Ovarian follicular fluids (FFs) contain several kinds of regulatory factors that maintain a suitable microenvironment for oocyte development. Extracellular vesicles (EVs) are among the factors that play essential roles in regulating follicle and oocyte development through their cargo molecules that include microRNAs (miRNAs). This study aimed to investigate small-EV (s-EV) miRNAs in porcine FFs and their potential association with oocyte quality. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…24,25 Small EVs (sEVs) contain miRNAs and are widely used as reliable biomarkers. 26 In a recent study, compared with healthy controls, colorectal cancer patients showed significantly increased miR-222-3p levels in plasma, which decreased effectively after surgical tumor removal. 27 Circulating sEV-derived miR-222-3p can serve as a promising noninvasive diagnostic biomarker for inflammatory breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…24,25 Small EVs (sEVs) contain miRNAs and are widely used as reliable biomarkers. 26 In a recent study, compared with healthy controls, colorectal cancer patients showed significantly increased miR-222-3p levels in plasma, which decreased effectively after surgical tumor removal. 27 Circulating sEV-derived miR-222-3p can serve as a promising noninvasive diagnostic biomarker for inflammatory breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…FF-EVs primarily reflect oocyte quality through its content ( Rodrigues et al, 2019 ; Battaglia et al, 2020 ). For example, because the amount and type of miRNA and lipid carried by FF-EVs differ between high and low quality follicles ( da Silveira et al, 2021 ; Gad et al, 2022 ; Zhang et al, 2021 ), miRNA expression in FF-EVs differ between oocytes with and without successful fertilization ( Martinez et al, 2018 ). Thus, we were able to assess oocyte developmental potential and fertilization ability using FF-EVs.…”
Section: Extracellular Vesicles’ Clinical Utility In Assisted Reprodu...mentioning
confidence: 99%
“…As a result, maternal RNAs that accumulate in the oocyte are required for chromatin reorganization and transcription factor translation (Eckersley-Maslin et al, 2018;Østrup et al, 2012). Despite attempts to estimate oocyte potential using mural granulosa, cumulus cells, extracellular vesicles from follicular fluid, and other follicular niche components, results are conflicting and unable to correlate precisely which molecules in the ooplasm are responsible for the oocyte's ability to develop to the blastocyst stage (Gad et al, 2022;Martínez-Moro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%